Planet of the Apes : Dawn of the Planet of the Apes - Reeves, Matt, 1966-; Clark, Dylan; Chernin, Peter, 1951-; Jaffa, Rick; Bomback, Mark; Silver, Amanda; Serkis, Andy; Oldman, Gary; Clarke, Jason, 1969-; Russell, Keri, 1976-; Greer, Judy, 1975-; Smit-McPhee, Kodi; et al. (Beverly Hills, California Twentieth Century Fox Home Entertainment, LLC, 2014)
A growing nation of genetically evolved apes led by Caesar is threatened by a band of human survivors of the devastating virus unleashed a decade earlier. They reach a fragile peace, but it proves short-lived, as both sides are brought to the brink of a war that will determine who will emerge as Earth's dominant species.
Sequel to: Rise of the planet of the apes. -Special features: Andy Serkis: rediscovering Caesar; Gallery. -- Credits:Directed by Matt Reeves. -Andy Serkis, Gary Oldman, Jason Clarke, Keri Russell, Judy Greer, Kodi Smit-McPhee, Kevin Rankin, Toby Kebbell, Kirk Acevedo, Enrique Murciano. -A growing nation of genetically evolved apes led by Caesar is threatened by a band of human survivors of the devastating virus unleashed a decade earlier. They reach a fragile peace, but it proves short-lived, as both sides are brought to the brink of a war that will determine who will emerge as Earth's dominant species. -DVD; PAL, region 4; anamorphic widescreen (1.85:1) presentation; Dolby Digital 5.1.
Wide screen (1.85:1).
Based on characters created by Rick Jaffa and Amanda Silver.
DVD release of the 2014 motion picture.
Special features: Andy Serkis: rediscovering Caesar ; gallery.
Music, Michael Giacchino ; editors, William Hoy, Stan Salfas ; director of photography, Michael Seresin.
Andy Serkis, Gary Oldman, Jason Clarke, Keri Russell, Judy Greer, Kodi Smit-McPhee, Kevin Rankin, Toby Kebbell, Kirk Acevedo, Enrique Murciano.
Keywords: Apes -- Drama; Transgenic animals -- Drama; War -- Drama; Video recordings for the hearing impaired; Science fiction films; Fiction films; Feature films; Action and adventure films; DVDs; Sci-Fi.; Feature films -- United States; Drama